2020
DOI: 10.1111/jfd.13309
|View full text |Cite
|
Sign up to set email alerts
|

A novel Dicistro‐like virus discovered in Procambarus clarkii with “Black May” disease

Abstract: The peak period of morbidity and death in cultured Procambarus clarkii is around May each year and is called the “Black May” disease. The pathogen causing “Black May” disease is believed to be a white spot syndrome virus (WSSV). In 2018, a significant number of P. clarkii died in the pond culture of Xinglong Township, Xuyi County. Two sampling tests on the affected pond showed that, in addition to WSSV, a novel Dicistro‐like virus (PcDV) was present. Genomic sequence analysis indicated that this new virus belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Temperature is an important factor that affects pathogen transmission. Many aquatic animal diseases occur in predictable seasons and temperatures (Huang et al, 2021;Pérez-Castañeda & Defeo, 2005;Shocket et al, 2018). We found that 'milky disease' of E. sinensis was mainly prevalent in winter when temperatures were below 4°C under the ice in the overwintering pond, which was consistent with the pattern of infections of M. bicuspidata in Macrobrachium rosenbergii (Chen et al, 2007).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Temperature is an important factor that affects pathogen transmission. Many aquatic animal diseases occur in predictable seasons and temperatures (Huang et al, 2021;Pérez-Castañeda & Defeo, 2005;Shocket et al, 2018). We found that 'milky disease' of E. sinensis was mainly prevalent in winter when temperatures were below 4°C under the ice in the overwintering pond, which was consistent with the pattern of infections of M. bicuspidata in Macrobrachium rosenbergii (Chen et al, 2007).…”
supporting
confidence: 80%
“…Temperature is an important factor that affects pathogen transmission. Many aquatic animal diseases occur in predictable seasons and temperatures (Huang et al, 2021; Pérez‐Castañeda & Defeo, 2005; Shocket et al, 2018). We found that ‘milky disease’ of E .…”
Section: Sampling Location Culture Area (Hectare) Sampled Households ...mentioning
confidence: 99%
“…to cause larval mortality ( Payne et al, 2007 ), which also has been found in other marine invertebrates ( Brigmon and Ridder, 1998 ). The peak period of morbidity and death in cultured P. clarkii is around May each year and is called the “Black May” disease; this disease presents with decreased crayfish activity and feeding, weakness, failure to molt, fluid build-up in the carapace and jejunum, and other features ( Huang et al, 2020 ). Whether the high abundance of Thiothrix during the juvenile period is related to the high mortality rate during molting needs further investigation.…”
Section: Discussionmentioning
confidence: 99%